Returns and Recalls in Julius Ocwinyo’s Fate of the Banished and Footprints of the Outsider - Balitumye, Michael (Lexicon, 2024)
The generic treatment of analepsis as a narrative technique has left some of its sub-aspects, like returns and recalls, understudied. Returns and recalls were first introduced by Gerald Genette (1980) as analepses drawn from the same line of action as the first narrative. Returns fill in after the event, a gap in the narrative while recalls constitute the narrative’s allusion to its past. By extension, therefore, they are posterior to the start of the first narrative and anterior to its end. Recalls and returns get a raw deal from narrative critics and theorists; one hardly finds an article-long discussion of these aspects, even in books primarily about narrative time. Yet, rarely if ever, do novelists craft a narrative without incidents of returns and recalls; hardly do real-life stories unfold without them. Adopting an interpretive paradigm, this paper analyzed returns and recalls and their functioning in Julius Ocwinyo’s Fate of the Banished and Footprints of the Outsider. This paper embraced a qualitative research approach; specifically, a descriptive case study design was deployed. Data was collected through close reading and documentary analysis; the paper was anchored on the Genettian discoursal perspective of narrative theory.